“You Started the Dispute” – an Essential Argument in Controversies Typical of Oral Cultures and the Discoursive Blueprint of the "Iliad" - Zieliński, Karol (Collectanea Philologica, 2024)
The paper argues that in the imagery found in the narrative context of the Iliad, the image of public debates is involved. Especially the argument “you started the dispute” is emphasized because it is connected with the concept of blame attributed to Paris and all the Trojans. Under the influence of such works like Graeber and Wengrow (2021), that shed a new light on the prehistory of mankind, I postulate a change in the paradigm of the interpretation of the Homeric world. I believe it would be much more comprehensible if interpreted as expressing egalitarian relations. After all, social and political circumstances described in the Iliad correspond to the phase in which hierarchy is only an increasing tendency. Comparisons drawn from other egalitarian cultures indicate how significant it is who started the dispute and how this argument can be cancelled. In the blueprint of the Iliad, however, Paris’ blame defines the meaning of the Trojan story and, therefore, the indictment that it was Alexander who started the dispute plays a paramount role.